Recrystallized NaCl from Thin Film to Nano-/Microsized Sacrificial Crystal for Metal Nanostructures - Lee, Dong Kyu; Kim, Tae Soo; Choi, Jae Young; Yu, Hak Ki (Crystal Growth and Design, 2018)
We developed a breakthrough method for preparing metallic nanostructures using a self-assembled NaCl nanosized sacrificial crystal and applied it to (i) transparent flexible electrodes and (ii) as catalysts for Si nanorod fabrication. Au nanostructures fabricated using the NaCl sacrificial crystal on a polyethylene terephthalate substrate showed low resistance (40 ω/sq), relatively high transmittance (73%), and excellent mechanical stability. Wet chemical etching of Si with Ag nanostructures formed on a Si(100) substrate using the NaCl sacrificial crystal produced uniform vertical Si microrods with a thickness of 1-2 μm and length of about 3-4 μm. These Si microrods showed high light absorption (over 90%) in the wavelength range of 350-800 nm, and various applications in optoelectronic devices are expected in the future.
Keywords: Au nanostructure; Flexible electrodes; High transmittance; Low resistance; Metal nanostructure; Metallic nanostructure; Si (100) substrate; Wavelength ranges